Do Czech companies disclose revenue in accordance with IFRS requirements? - Kateřina Knorová (European Financial and Accounting Journal, 2016)
Revenue is one of the key indicators informing users of financial statements about company's performance. The different approaches to revenue recognition are analysed in the first part of this paper. The second part addresses the convergence of US GAAP and IFRS in the area of revenue recognition and examines the new converged revenue standard IFRS 15. The third part focuses on the IFRS disclosure requirements set by the current standard IAS 18 and compare to the new ones defined by IFRS 15. The empirical study analyses consolidated financial statements of Czech listed companies and assesses the compliance with current revenue disclosure IFRS requirements.
Keywords: M41; 650; IAS 18; IFRS 15; Revenue disclosure; Revenue recognition